Phylogenetic Analysis of the Plant U2 snRNP Auxiliary Factor Large Subunit A Gene Family in Response to Developmental Cues and Environmental Stimuli - Lu, Shuai; Gao, Cong; Wang, Yongzhou; He, Yingying; Du, Junrong; Chen, Moxian; Zhao, Hua; Fang, Hui; Wang, Baohua; Cao, Yunying (Frontiers in Plant Science, 2021)
In all organisms, splicing occurs through the formation of spliceosome complexes, and splicing auxiliary factors are essential during splicing. U2AF65 is a crucial splicing cofactor, and the two typical RNA-recognition motifs at its center recognize and bind the polypyrimidine sequence located between the intron branch site and the 3′-splice site. U2AF65A is a member of the U2AF65 gene family, with pivotal roles in diseases in mammals, specifically humans; however, few studies have investigated plant U2AF65A, and its specific functions are poorly understood. Therefore, in the present study, we systematically identified U2AF65A in plant species from algae to angiosperms. Based on 113 putative U2AF65A sequences from 33 plant species, phylogenetic analyses were performed, followed by basic bioinformatics, including the comparisons of gene structure, protein domains, promoter motifs, and gene expression levels. In addition, using rice as the model crop, we demonstrated that the OsU2AF65A protein is localized to the nucleus and cytoplasm, and it is involved in responses to various stresses, such as drought, high salinity, low temperature, and heavy metal exposure (e.g., cadmium). Using Arabidopsis thaliana and rice mutants, we demonstrated that U2AF65A is involved in the accumulation of plant biomass, growth of hypocotyl upon thermal stimulation, and reduction of tolerance of high temperature stress. These findings offer an overview of the U2AF65 gene family and its stress response functions, serving as the reference for further comprehensive functional studies of the essential specific splicing cofactor U2AF65A in the plant kingdom.